Recent Advances in Organocatalyzed Asymmetric Reduction of Prochiral Ketones: An Update - Qin, Xu-Long; Xu, Li-Jun; Han, Fu-She (Synthesis, 2022)
Chiral alcohols are important synthetic intermediates and building blocks for the synthesis of drugs, agrochemicals, and natural products. Asymmetric reduction of prochiral ketones has been the most investigated method for accessing chiral alcohols. In this regard, organocatalyzed asymmetric reduction, as a complementary method to transition-metal- and enzyme-catalyzed reactions, has attracted tremendous interest in the past decades due to the reactions with such catalysts being metal-free and easy to operate, and principally, the ease of recovery and the ability to reuse the catalysts. Following up on a comprehensive overview on organocatalyzed asymmetric reductions of prochiral ketones in early 2018, this short review is intended to summarize the recent progress in this area from the beginning of 2018 until the end of August 2021.1 Introduction2 Boron-Based Chiral Organocatalysts2.1 Boron-Containing Chiral Schiff Base Catalysts2.2 Chiral Alpine-Borane Catalysts2.3 Boron-Containing Chiral Frustrated Lewis Pair Catalysts2.4 Chiral Borate Ester–Amine Complex Catalysts3 Phosphorus-Based Chiral Organocatalysts3.1 Chiral Phosphoric Acid Organocatalysts3.2 Chiral Phosphinamide and Phosphoramide Organocatalysts4 Chiral Ionic Liquid Organocatalysts5 Chiral-Oxazoline-Based Organocatalysts6 Conclusion and Outlook
Keywords: asymmetric reduction; prochiral ketones; organocatalysts; chiral alcohols